The repeat region of cortactin is intrinsically disordered in solution. Issue 1 (December 2017) - Li, Xiaofeng; Tao, Yeqing; Murphy, James; Scherer, Alexander; Lam, TuKiet; Marshall, Alan; Koleske, Anthony; Boggon, Titus
Abstract The multi-domain protein, cortactin, contains a 37-residue repeating motif that binds to actin filaments. This cortactin repeat region comprises 6½ similar copies of the motif and binds actin filaments. To better understand this region of cortactin, and its fold, we conducted extensive biophysical analysis. Size exclusion chromatography with multi-angle light scattering (SEC-MALS) reveals that neither constructs of the cortactin repeats alone or together with the adjacent helical region homo-oligomerize. Using circular dichroism (CD) we find that in solution the cortactin repeats resemble a coil-like intrinsically disordered protein. Small-angle X-ray scattering (SAXS) also indicates that the cortactin repeats are intrinsically unfolded, and the experimentally observed radius of gyration (R g ) is coincidental to that calculated by the program Flexible-Meccano for an unfolded peptide of this length. Finally, hydrogen-deuterium exchange mass spectrometry (HDX-MS) indicates that the domain contains limited hydrophobic core regions. These experiments therefore provide evidence that in solution the cortactin repeat region of cortactin is intrinsically disordered.